Prognostic and immunological role of SERPINH1 in pan-cancer - Zhong, Huage; Wang, Zheng; Wei, Xiaoxia; Liu, Yaning; Huang, Xiaoliang; Mo, Xianwei; Tang, Weizhong (Frontiers in Genetics, 2022)
Background: SERPINH1 gene plays a vital part in tumorigenesis and development, whereas its potential as an immunotherapy target is still unknown. Hence, this research aimed to probe into the roles of SERPINH1 in human tumors. Method：Using The Cancer Genome Atlas (TCGA), Genotype-Tissue Expression (GTEx) database, Oncomine and SangerBox software, the pan-cancer expression of SERPINH1 and its correlation were systematically analyzed. SERPINH1 protein information was detected by Human Protein Atlas (HPA) database and String database. The genomic alterations of SERPINH1 were studied using the c-BioPortal database. The influence of SERPINH1 on prognosis was analyzed by Kaplan-Meier plotter. The R package "clusterProfifiler" was used for enrichment analysis to detect the role of SERPINH1. The TIMER2 database was used to further analyze the correlation between the immune cell infiltration score of TCGA samples and the expression of SERPINH1. Results: SERPINH1 overexpression was related to worse survival status in pan-cancer. And high expression of SERPINH1 was positively associated with tumor stage and poor prognosis. Moreover, SERPINH1 played an important role in tumor microenvironment and immune regulation. Our study revealed that SERPINH1 expression has a strong correlation with immune cell filtration, immune regulation, chemokines and immune checkpoints. Conclusion: Our research found that SERPINH1 was a risk factor and predictor of poor prognosis in various tumors. High expression of SERPINH1 may contribute to tumor immune-suppressive status. And SERPINH1 may become a potential immunotherapy target in pan-cancer.